Chemically Contaminated Eel Fed to Pregnant and Lactating Mouse Dams Causes Hyperactivity in Their Offspring - Dridi, Imen; Soualeh, Nidhal; Bohn, Torsten; Soulimani, Rachid; Bouayed, Jaouad (International Journal for Vitamin and Nutrition Research, 2016)
International audience Abstract.This study examined whether perinatal exposure to polluted eels (Anguilla anguilla L.) induces changes in the locomotor activity of offspring mice across lifespan (post-natal days (PNDs) 47 – 329), using the open field and the home cage activity tests. Dams were exposed during gestation and lactation, through diets enriched in eels naturally contaminated with pollutants including PCBs. Analysis of the eel muscle focused on the six non-dioxin-like (NDL) indicator PCBs (Σ6 NDL-PCBs: 28, 52, 101, 138, 153 and 180). Four groups of dams (n = 10 per group) received either a standard diet without eels or eels (0.8 mg/kg/day) containing 85, 216, or 400 ng/kg/day of ϵ6 NDL-PCBs. The open field test showed that early-life exposure to polluted eels increased locomotion in female offspring of exposed dams but not in males, compared to controls. This hyperlocomotion appeared later in life, at PNDs 195 and 329 (up to 32 % increase, p < 0.05). In addition, overactivity was observed in the home cage test at PND 305: exposed offspring females showed a faster overall locomotion speed (3.6 – 4.2 cm/s) than controls (2.9 cm/s, p <0.05); again, males remained unaffected. Covered distances in the home cage test were only elevated significantly in offspring females exposed to highest PCB concentrations (3411 ± 590 cm vs. 1377 ± 114 cm, p < 0.001). These results suggest that early-life exposure to polluted eels containing dietary contaminants including PCBs caused late, persistent and gender-dependent neurobehavioral hyperactive effects in offspring mice. Furthermore, female hyperactivity was associated with a significant inhibition of acetylcholinesterase activity in the hippocampus and the prefrontal cortex.